Land Hunting and Hunting Culture in Hassa District - Ömer İlyas Delibekir; Gönül Reyhanoğlu (Uluslararası Halkbilimi Araştırmaları Dergisi)
Hunting has been one of the occupations that met the basic needs of nutrition and movement. In later periods, in addition to the need for nutrition and movement.Today, the function of preparing for military service has disappeared in modern hunting. It continues to meet the basic need for nutrition, albeit to a lesser extent. However, hunting, which continues to satisfy the basic need for movement, exists as a sport and hobby. The fact that land hunting continues to preserve its tradition in the district of Hatay, Hassa, has been effective in the decicision of the study subject. The data of the study were obtained by field observation and interview, using the snowball technique, which are qualitative research methods. The structure of the tradition that has survived to the present day as a profession, master-apprentice relationship, practices, dogs, tools and equipment, beliefs, place in the cultural structure, game meat and sharing, function and transformation were examined without overlooking the fact that it is an execution, with a functional perspective on the information obtained. The collection of findings was limited to the years 2022-2024. In Hassa, it is seen that practice is realized as a hobby rather than a free or spare time activity, but some hunters who are trained in a master-apprentice relationship continue this culture as a traditional profession with certain beliefs and practices from the past to the present. In addition, hunting cuisine specific to the products obtained from the hunt has developed in the region.